ASSOCIATIVISMO EMPRESARIAL ENTRE MICRO E PEQUENAS EMPRESAS: A EXPERIÊNCIA DO GRANDE ABC COM O PROJETO EMPREENDER (SEBRAE) - Foltran, Leandro Henrique Mariano (2009)
Corporate associativism has been a way of local development, in economical, social or cultural ways and is a great ally to the beginning and development of micro and small enterprises. This matter has been experienced and studied by several countries in the world, among them European countries specifically Italy, although it has not been much studied and known in Brazil yet. This research aimed to analyze the corporate associativism among micro and small sized enterprises (MSEs) in the Endeavor Project (Projeto Empreender SEBRAE) in the Great ABC area (Região do Grande ABC GABC), relating its data with the ones published on the 2003/5 report from The Observatory of Europeans Small and Medium sized Enterprises, to analyze the ways that associativism is done in Brazil, also identifying the participating enterprises and entrepreneurs profiles. To do that, a tool developed by The Observatory of Europeans SMEs was used to collect information of 63 participating companies of the Endeavor Program from the center of Santo André, São Caetando do Sul e Ribeirão Pires, in the GABC. It was necessary to analyze the data gathered in the GABC, comparing it to the European data to find converging and diverging points in each experience, in order to gain knowledge and develop the subject. Choosing the GABC area, has been motivated by its economical changes, going from big industries pole and cradle to a great center of small services enterprises. After collecting and analyzing the data, we noticed that GABC s, and European s, specifically in Italy, experience converge in many aspects, in spite of the fact that they have many structural differences. While an organ from the European Union is responsible for their project, in Brazil, SEBRAE has been facing great conflicts with the local Commercial and Industrial Associations (Associações comerciais e industriais ACIs) on the matter of distributing the people and structure expenses involved in the project implementation. Besides that, the towns need to get closer to the project, in the face that it could encourage other enterprises to join the program and also help the system to get more serious. There are two other points that deserves to be highlighted. First, is the fact that Project Endeavor has a low local exposure, and secondly that the development agency from GABC (Agência de Desenvolvimento do Grande ABC) does not participate closely in the project. At last, some data has came up during the research, breaking all barriers from management theories known, such as friendship being a factor of associativism. Therefore, the results obtained in this research points to the influence of the incentive in the associativist process development in the GABC area, serving also as an encouragement to bring other social elements in the process closer.(AU)